On the effects of factor mobility on local infrastructure policy and rent-seeking - Jens Oliver Lorz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
This paper deals with the influence of factor mobility on local infrastructure policy and rent-seeking activities of local interest groups. It employs a model where households differ with respect to their endowment with the immobile factor land. Local governments decide about the level of productive infrastructure in their jurisdiction. According to their land endowment, different households benefit to a different degree from the infrastructure. This redistribution effect of local infrastructure gives households an incentive for rent-seeking: Landabundant households seek to influence their government to increase the level of infrastructure whereas land-poor households seek to influence their government to reduce the infrastructure level. As this paper shows, factor mobility and fiscal competition between local governments lead to increasing rent-seeking expenditures for a broad class of cases.
Keywords: D72; H41; H72; 330; Factor Mobility; Fiscal Competition; Rent-Seeking; Kommunale Infrastruktur; Grundbesitz; Bodenrente; Rent Seeking; Faktormobilität; Steuerwettbewerb; Theorie